Towards an Omnichannel Education: A Case Study of Undergraduate Marketing Students in Central Mexico - Gutierrez Leefmans, Catalina (2024)
Since the onset of the COVID-19 pandemic, technologically mediated communication channels have evolved significantly, particularly in education. Given the large number of channels used in the teaching-learning process by university students, and acknowledging their diverse cognitive channels, efficiency is essential. This study aims to evaluate omnichanneling as a resource for achieving effective learning in higher education students. The study began with a series of integrated activities utilizing various communication channels, as part of an exploratory-descriptive research conducted with 56 university marketing students. Over the course of one semester, activities were developed using an omnichannel format, and a survey was conducted at the end of the course to evaluate the applied methodology. The use of omnichanneling in the classroom is proposed as an innovative and effective educational strategy, integrating learning activities that consider both digital and face-to-face media through a case study that identifies and leverages the advantages offered by each channel. Among the most significant findings, the use of educational omnichanneling is perceived as yielding positive learning outcomes and is favorably accepted by students.